Psychodynamic self psychology in the treatment of anorexia and bulimia - Bachar, Eytan; Verbin, Analu (London : Routledge, 2020)
This book presents an implementation of psychodynamic self psychology in the treatment of anorexia nervosa and bulimia nervosa, using a theoretical and therapeutic approach to examine the way that patients turn to food consumption or avoidance in order to supply needs they do not believe can be provided by human beings. The book starts with an overview of self psychology, presenting both the theory of self psychology and its specific application for the etiology and treatment of eating disorders. Featuring contributions from eating disorder professionals, the book then integrates this theory with16 compelling case studies to explore how the eating-disordered patient is scared to take up space in a society that encourages precisely that. Professionals in the field of psychotherapy for eating disorders, as well as the entire community of psychotherapists, will benefit from the empirical capability of the theory to predict the development as well as remission from eating disorders.
OCLC-licensed vendor bibliographic record.
Keywords: Anorexia nervosa -- Treatment; Bulimia -- Treatment; Psychodynamic psychotherapy; Self psychology; PSYCHOLOGY / Psychopathology / Eating Disorders; PSYCHOLOGY / Mental Health